Optimalisasi Kinerja Organisasi Perangkat Daerah (OPD) Melalui Good Governance Diperkuat oleh Budaya Oganisasi (Studi Empiris OPD Kota Solok) - Hiya, Nori Fetty; Maison, Witra; Defitri, Siska Yulia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to find out, in Solok, how good governance affects the efficiency of the regional apparatus organization through the mediation effect of organizational culture. The primary data for this study came from a questionnaire. The sample of this study includes the head and secretary of the OPD in the Solok city area. Utilizing the SmartPLS 3.0 program, SEM-PLS is an analytical approach used. The findings of this study show that good governance in Solok does not affect the efficiency of the regional apparatus organization, and the influence of good governance on efficiency does not moderate the organizational culture in the city.